The Effect of Financial Literacy on Investment Decision-Making among MSME Actors: An SPSS Analysis - Muliana, Muliana (LPPPIPublishing, 2025)
This study aims to analyze the effect of financial literacy on investment decision-making among Micro, Small, and Medium Enterprises (MSME) actors. The research adopts a quantitative approach with a survey method, using a structured questionnaire as the primary data collection tool. A total of 120 MSME respondents were selected through purposive sampling to ensure their relevance to the study objectives. Data were analyzed using SPSS 27 with regression analysis to test the relationship between the independent and dependent variables.The findings indicate that financial literacy has a significant positive effect on investment decision-making among MSME actors. Respondents with higher levels of financial literacy tend to make more rational, informed, and profitable investment choices compared to those with lower levels of financial knowledge. These results highlight the importance of strengthening financial education and awareness programs for MSMEs to improve their decision-making capabilities. This study contributes to the literature on financial management by emphasizing the crucial role of financial literacy in supporting sustainable MSME development.